How additive manufacturing allows products to absorb variety in use: empirical evidence from the defence industry. Issue 2 (17th February 2022) - Davies, Philip; Parry, Glenn; Alves, Kyle; Ng, Irene
Abstract: The normative assumption holds that a product's structural and functional elements are fixed pre-production to support manufacturing efficiency. Firms servitizing are faced with delivering resources for customers in context and absorbing contextual variety presents a number of challenges. This paper examines shortcomings of modular design and whether additive manufacturing can efficiently provides high variety that meets emergent user demand. A case study is undertaken, drawing upon design change data and in-depth interviews with industry experts. Findings show that introducing design changes to modular products through life creates complexity in the product architecture and the supply chain. We find that AM can act as a supply chain solution, managing complexity and allowing products and supply chains to efficiently and effectively absorb contextual variety. Existing theory must expand beyond the normative assumption that the physical product is fixed, to include cases where the tangible product can absorb variety to meet the emergent need.